Accent On Nouns And Its Reference Coding In Siwi Berber (Egypt) - SCHIATTARELLA, Valentina (My University, 2020)
The aim of this article is to investigate the position of the accent on nouns in Siwi, a Berber language spoken in the oasis of Siwa, Egypt, and to see how its alternation on the last or penultimate syllable functions in terms of reference coding. In Siwi, the role of the accent placed on nouns goes beyond the field of phonology: an analysis of original data from both spontaneous discourse and elicitations will show its functions in terms of attribution of (in)definiteness of nouns, in different environments. In order to proceed with the analysis, it is worth noting that Siwi, like all other Berber languages, does not have definite or indefinite articles.
Keywords: Siwi Berber; nouns; Egypt